2010
DOI: 10.1673/031.010.3601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insecticide Regimens on Biological Control of the Tarnished Plant Bug,Lygus lineolaris, byPeristenusspp. in New York State Apple Orchards

Abstract: To improve biological control of Lygus lineolaris (Palisot de Beauvois) (Hemiptera: Miridae), the European parasitoid Peristenus digoneutis Loan (Hymenoptera: Braconidae) was introduced into the US in the 1980's and has become established in forage alfalfa, strawberries and apples. The objective of this study was to determine how four different insecticide management regimes affected parasitism of L. lineolaris by Peristenus spp. During the summers of 2005 and 2006, L. lineolaris nymphs were collected from New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Most of these newer reduced risk insecticides are target specific, but there is evidence that some of these insecticides could affect key natural enemies that regulate secondary insect and mite pests (Agnello et al, 2009;Shearer, 2013a, 2013b;Brunner et al, 2001;Crampton et al, 2010;Kim et al, 2006;Myers et al, 2006;Walgenbach, 2005, 2006). In contrast to neurotoxic OP insecticides, some of the newer reduced risk insecticides have been shown to have sublethal rather than lethal effects on natural enemies Shearer, 2013a, 2013b;Beers and Schmidt, 2014;Desneux et al, 2007;Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these newer reduced risk insecticides are target specific, but there is evidence that some of these insecticides could affect key natural enemies that regulate secondary insect and mite pests (Agnello et al, 2009;Shearer, 2013a, 2013b;Brunner et al, 2001;Crampton et al, 2010;Kim et al, 2006;Myers et al, 2006;Walgenbach, 2005, 2006). In contrast to neurotoxic OP insecticides, some of the newer reduced risk insecticides have been shown to have sublethal rather than lethal effects on natural enemies Shearer, 2013a, 2013b;Beers and Schmidt, 2014;Desneux et al, 2007;Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…8 Even though it is environmentally friendly, some studies reported that it still has some harmful effects, especially in agricultural system. 9,10 Furthermore, possible improper use during a harvest period could result in a level of residues being harmful to humans. Misuses could lead the rapid development of pest resistance.…”
Section: Introductionmentioning
confidence: 99%